2007
DOI: 10.1182/asheducation-2007.1.179
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence-Based Use of FFP and Cryoprecipitate for Abnormalities of Coagulation Tests and Clinical Coagulopathy

Abstract: There continues to be a general but unfounded enthusiasm for fresh frozen plasma (FFP) or frozen plasma (FP) usage across a range of clinical specialties in hospital practice. Plasma for transfusion is most often used where there are abnormal coagulation screening tests, either therapeutically in the face of bleeding, or prophylactically in nonbleeding patients prior to invasive procedures or surgery. Little evidence exists to inform best therapeutic transfusion practice, and most studies describe plasma use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 50 publications
(46 reference statements)
0
104
0
3
Order By: Relevance
“…Stanworth and co-workers reviewed 12 studies of FP use in the NICU, and concluded that no benefit of FP could be identified in non-bleeding patients, for its use either as a volume expander, for immunological effects or for preventing hemorrhage. 21,22 In the present study, we identified 456 transfusions, during a one-year period, that were given in violation of our transfusion guidelines. We speculate that some of these transfusions conveyed little or no benefit to the recipient, but each unneeded transfusion conveyed known and unknown risks.…”
Section: Discussionmentioning
confidence: 99%
“…Stanworth and co-workers reviewed 12 studies of FP use in the NICU, and concluded that no benefit of FP could be identified in non-bleeding patients, for its use either as a volume expander, for immunological effects or for preventing hemorrhage. 21,22 In the present study, we identified 456 transfusions, during a one-year period, that were given in violation of our transfusion guidelines. We speculate that some of these transfusions conveyed little or no benefit to the recipient, but each unneeded transfusion conveyed known and unknown risks.…”
Section: Discussionmentioning
confidence: 99%
“…57 Allergic reactions to FFP are common, with a frequency of 1%-3% of all transfusions, and can be a cause of frequent morbidity and a potential risk of mortality in multiply transfused patients. 58 Infectious risks with known agents such as HIV, hepatitis B, and hepatitis C are low, but the rate of prion transmission via transfusion of blood products, while probably low, remains unknown. 56,58,59 Significant concern has been raised about increased vascular volume and fluid overload after FFP infusions causing increased bleeding.…”
Section: Ffpmentioning
confidence: 99%
“…58 Infectious risks with known agents such as HIV, hepatitis B, and hepatitis C are low, but the rate of prion transmission via transfusion of blood products, while probably low, remains unknown. 56,58,59 Significant concern has been raised about increased vascular volume and fluid overload after FFP infusions causing increased bleeding. 24 In a randomized trial comparing a restrictive transfusion policy (that maintained a low central venous pressure) with liberal transfusion during liver transplantation, Feng et al showed that the restrictive policy led to a significant reduction in intraoperative blood loss and transfusion requirements.…”
Section: Ffpmentioning
confidence: 99%
“…However, there is little evidence to support the efficacy of frozen plasma in these circumstances or to define criteria for the degree of coagulopathy required before any benefit can be expected. 2 Coagulation screening assays have little value in predicting bleeding associated with invasive procedures in patients with mild to moderate coagulopathy 5 (international normalized ratio 1.5-3.0), and transfusion of frozen plasma has a negligible effect on correcting trivial coagulation abnormalities (international normalized ratio < 1.5). 6 The dose of frozen plasma required to effect major reductions in substantially prolonged clotting times is considerable (15-20 mL/kg) 7 and poses a risk of circulatory overload.…”
mentioning
confidence: 99%
“…We have compiled broad categories of appropriate and inappropriate indications for use of frozen plasma (Box 1) from critical reviews 2 and various published guidelines. 1,3,4 Frozen plasma is usually prescribed to correct coagulopathy from various causes, as identified from laboratory test results, with or without bleeding or expected invasive procedures.…”
mentioning
confidence: 99%